The Jesuits in ’Historie církevní‘ by Pavel Skála of Zhoř and Their Possible Role in Skála’s View on History (Theatrum historiae, 2020)
’Historie církevní’(The History of the Church) by Pavel Skála of Zhoř is probably the most extensive Czech early modern historiographical work, moreover, preserved in only one manuscript. Being written by a protestant author, ’Historie církevní’ contains rather a detailed image of the Jesuit Order hidden within its text. The Jesuits were presented by Skála through a collection of various motives connected to the Order, which also allowed him to create his own image of the Order. The article focuses on the parts of Skála’s manuscript dealing with the Jesuits and their possible role in his view on history.
Keywords: Czech early modern historiography; protestant historiography; history of the church; Jesuit order; Jesuits; Jesuiten–Fabeln; early modern period; 17th century